Fairly rare clear cell adenocarcinoma mimicking liver cancer: a case report - Norifumi Harimoto; Kei Hagiwara; Takahiro Yamanaka; Norihiro Ishii; Takamichi Igarashi; Akira Watanabe; Norio Kubo; Kenichirou Araki; Hayato Ikota; Masafumi Suyama; Takeshi Maki; Shinichi Aishima; et al. (Surgical Case Reports, 2018)
Abstract Background Clear cell carcinoma commonly occurs in the ovary and kidney, and clear cell cholangiocarcinoma was rarely reported. Differential diagnosis which the origin of the tumor located on the liver surface is intrahepatic or extrahepatic was difficult. Herein, we report a case of clear cell adenocarcinoma mimicking liver cancer. Case presentation This was a 55-year-old female who had the tumor with cystic component in the liver. She was performed hepatectomy and diagnosed as clear cell adenocarcinoma. Histopathological evaluation revealed intra-cystic clear cell adenocarcinoma. The tumor has ductal structure including mucin and atypical nuclear with clear cytoplasm. The tumor was separated from the liver and the diaphragm. The expression of Pax8 was positive, but the expression CK7 and HNF1β was positive and that of CD10 and ER was negative, which indicate that the tumor has the feature of clear cell carcinoma of ovary, not renal cell carcinoma nor cholangiocarcinoma. Conclusions Our experience with this patient suggests that this tumor may originate from the endometriosis onto the diaphragm from the detailed results of immunohistochemical staining.